Everolimus or sunitinib as first-line treatment of metastatic papillary renal cell carcinoma: A retrospective study of the GETUG group (Groupe d'Etude des Tumeurs Uro-Génitales). (November 2021) - Cancel, Mathilde; Fromont, Gaelle; Blonz, Cyriac; Chevreau, Christine; Rioux-Leclercq, Nathalie; Laguerre, Brigitte; Oudard, Stéphane; Gross-Goupil, Marine; Gravis, Gwenaelle; Goldwasser, François; Rolland, Frédéric; Delva, Rémy; et al.
Abstract: Background: Two phase II trials (NCT00688753 and NCT00541008) reported efficacy data of sunitinib and everolimus in first-line treatment of metastatic papillary renal cell carcinoma (mpRCC). Although most patients receive sunitinib or a mammalian target of rapamycin (mTOR) inhibitor in first- and second-line treatment, the optimal strategy remained unknown. Material and methods: In 23 centres of the Groupe d'Etude des Tumeurs Urogénitales group, after centralised pathological review, we analysed retrospectively progression-free survival (PFS) of patients with mpRCC treated in first-line treatment (PFS-1) with sunitinib or everolimus (primary end-point), PFS in second-line treatment (PFS-2), overall survival (OS), objective response rate, disease control rate (DCR), overall sequence and prognostic factors for OS (secondary end-points). Results: One hundred thirty-eight patients (119 men and 19 women), median age 62.5 years, with mpRCC type 1 (n = 24) or non–type 1 (n = 114), received first-line sunitinib (n = 107) or everolimus (n = 31). With a median follow-up of 92 months, we found no significant difference between the treatment groups in terms of PFS-1 (5.5 versus 6.2 months) and DCR (69% versus 83%). Ninety-eight patients received a second-line treatment, 69% with mTOR inhibitors after sunitinib and 100% with tyrosine kinase inhibitors after everolimus, with similar DCR (64% versus 58%), median PFS-2 (3.4 versus 4.8 months) and OS (16.0 versus 20.3 months). No factor was prognostic for PFS-1, whereas leukocytosis, anaemia and the time from diagnosis to first systemic therapy < 1 year were prognostic for OS. We found no prognostic difference between both pRCC subtypes. The International Metastatic Renal Cell Database Consortium risk factors were prognostic for OS. Conclusion: Sunitinib and everolimus had similar efficacy in first-line treatment of patients with mpRCC. Highlights: This is the first study that compared retrospectively sunitinib and everolimus as first-line treatment in mpRCC patients. Sunitinib and everolimus have similar efficacy in first-line treatment of mpRCCs. The IMDC risk score is prognostic for overall survival in metastatic pRCCs.